ANALISIS POPULASI PERTUMBUHAN ALLOMETRI DAN INDEKS KONDISI Harpiosquilla Raphidea WAKTU TANGKAPAN SIANG HARI DI PERAIRAN JUATA KOTA TARAKAN - Kalalo, Alfreste; Salim, Gazali; wiharyanto, Dhimas (Jurnal Harpodon Borneo, 2015)
The research method uses descriptive method. H.raphidea shrimp sampling using a sampling method in area waters by fishermen catch jauta juata Tarakan city. Sampling using purposive sampling method performed 12 times with the consideration that the sampling of 12 times expected to represent the population of shrimp Harpiosquilla raphidea in the waters Juata Tarakan City. The main variables were measured in this study is the morphological Harpiosquilla raphidea shrimp is the carapace (carapace length), shrimp body length (total length) and the shrimp body weight (total weight and the weight of meat), and gender. The result showed a growth model based on relationship the total length with the total weight for shrimp gender Male and Female are allometri negative correlation value is very strong. A growth model based on carapace length relationship with the weight of meat to shrimp gender Male and Female are allometri negative correlation value is very strong and powerful. The percentage of the value of the condition index model based on the total length relationship with the total weight for the male sex Harpiosquilla raphidea obtained is the dominant body shape is shape flat whereas female sex condition index obtained is the dominant body shape is fat. The percentage of the value of the condition index model based on relationship carapace length with the weight of meat to Harpiosquilla raphidea male and female found is the dominant body shape body shape Slim. Sex ratio were obtained from a total of about 326 samples get the number of shrimp tails 203 are male and female pairs mantis shrimp as much as 123 birds. Sex ratio between males and females did not happen equilibrium which is 1.7: 1. The percentage obtained for shrimp ie by 62.3% male and 37.7% female shrimp. Keywords : population; growth; condition index; H.raphidea; Juata; Tarakan